Strategy to Strengthen the Resilience of Migrant Boat Crews in Taiwan - Nur Cholik Widyan Saputra; Margaretha Hanita; Stanislaus Riyanta (Publikasi Indonesia, 2024)
This study aims to understand the resilience strategies of migrant crew on Taiwanese fishing vessels in the face of stress and pressure at work. Using a qualitative approach, this study involved in-depth interviews with seven resource persons who were migrant fishermen in Taiwan. The snowball sampling technique was used to select interviewees who had previously worked on Taiwanese fishing vessels. Data collection was conducted through interviews to gain comprehensive insights into the experiences and resilience strategies of migrant fishermen. The results showed that migrant fishermen are exposed to various sources of stress and pressure in the workplace, including hazardous working conditions, distance from family and home, work pressure, and poor accommodation conditions. However, the study also revealed that migrant fishermen use a variety of resilience strategies to overcome these challenges, including social support from colleagues, independence in solving problems, improved adaptation skills, and finding sources of strength from personal beliefs and values. By deepening the understanding of migrant fishermen's resilience strategies on Taiwanese fishing vessels, the research is expected to provide valuable insights for developing policies and intervention programs to improve the welfare and safety of migrant fishermen in risky work environments. In addition, the findings of this study can also be a foundation for further research in understanding the dynamics and determinants of individual resilience in high-risk occupational sectors.